ORGANIZATIONAL DIMENSIONS OF THE COVID 19 TASK FORCE - Sudrajat, Tatang; Priadi, M. Dadi; Sikki, Nurhaeni; Wulandari, Wulandari; Imaniar W., Agnie (Jurnal Governansi, 2021)
Covid 19 that has hit the Indonesian nation has had a multidimensional impact on people's lives. The formation of the Task Force for the Acceleration of Handling Covid 19 is a concrete step for the government in response to this problem. The Task Force has certainly faced various obstacles, challenges and problems in carrying out its duties and functions. One of them will be related to the arrangement of the various dimensions of the Task Force organization in several laws and regulations that govern it. The research method used is descriptive and juridical normative with the aim of obtaining a complete and comprehensive description and evaluation of the organizational dimensions of the Task Force that have been stipulated in several laws and regulations as a product of public policy. The results showed that the Task Force as the operating core of government policies / programs dealing with Covid 19 was an ad hoc institution that was a political organization. Regulations for several structural and contextual dimensions are contained in Presidential Decree No. 7/2020, Presidential Decree No. 9/2020, Presidential Regulation No. 82/2020, and Decree of the Chair of the Task Force No. 16/2020, namely formalization, specialization, hierarchy of authority, organizational goals and organizational size.